1998
DOI: 10.1007/s11661-998-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on silicon particle damage in A356 alloy

Abstract: fringes due to double diffraction from (1-101) M2C reflections is presumably due to their relatively higher intensities resulting in intense double diffraction spots.An examination of the results of the present and previous studies on the secondary hardening high performance steels indicates the following.(1) The black-white strain contrast indicating coherency of the carbides with the ferrite matrix was observed only until the peak aging temperature of 482 ЊC.(2) The appearance of fringes in the M 2 C carbide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…It can be explained by the fact that the sample without vibration has the larger SDAS value and elongated eutectic silicon particles. The elongated eutectic silicon particles fracture more frequently than the spherical particles as they are the main sources of stress concentration [25][26][27]. Because the eutectic silicon particles are larger and cluster along both cell and grain boundaries, there is a nearly continuous wall of eutectic silicon particles around the dendrite cell.…”
Section: Methodsmentioning
confidence: 99%
“…It can be explained by the fact that the sample without vibration has the larger SDAS value and elongated eutectic silicon particles. The elongated eutectic silicon particles fracture more frequently than the spherical particles as they are the main sources of stress concentration [25][26][27]. Because the eutectic silicon particles are larger and cluster along both cell and grain boundaries, there is a nearly continuous wall of eutectic silicon particles around the dendrite cell.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that large and elongated silicon particles fracture more frequently than spherical particles [18][19][20][21]. In the case of thixoformed samples formed at 600 • C (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Considerable effort has been made recently to investigate the effect of Si particles on the mechanical and fatigue properties of cast Al alloys, both experimentally and numerically [1][2][3][11][12][13][14][15][16]. However, the influence of the fracture and debonding of Mg 17 Al 12 particles on the fatigue characteristics of Mg alloys has not been well investigated until now.…”
Section: Introductionmentioning
confidence: 99%